Maternal and perinatal outcomes in diabetic pregnancies at BPKIHS - Das, Anamika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Diabetes has become a global pandemic because of aging population, sedentary life style, urbanization, and increasing incidence of obesity; this study was aimed to identify the maternal and perinatal outcome in Diabetes complicating pregnancies and to compare the outcome in Gestational Diabetes Mellitus and Overt Diabetes Mellitus. Methods: This was a descriptive study conducted from 1st April 2013-31st March 2014 on total 75 pregnant women. All antenatally diagnosed cases of GDM and overt diabetes, booked or unbooked, whoever came for delivery were studied. Both mothers and neonates were followed up in ante-partum, intra-partum, and post-partum period till their stay in hospital. Management of the patient was done as per the hospital protocol. Results: Out of 75 cases enrolled, 25.33% had GDM and 16% had overt diabetes mellitus.57.33%patients were multigravida, among which 40% had GDM and 17.33% had Overt Diabetes Mellitus.61.33% patients underwent LSCS, of which 41.33% had GDM and 20% had overt diabetes mellitus. Obstetric complication was more common in GDM patients (30.66%) compared to Overt (22.66%). 89.33%babies had good neonatal outcome and 10.66% babies (6.66% of GDM mothers and 4% of overt mothers) had poor neonatal outcome (macrosomia, hypoglycaemia, prematurity, respiratory distress with NICU stay and use of antibiotics, poor APGAR (<7 at 5 min), gross congenital malformation, hyperbilirubinemia, stillbirth and neonatal death). Conclusions: Maternal and perinatal complications was commonly seen in diabetic pregnancy though more common in GDM.The time has come for the Government of Nepal to implement an effective plan to the benefit of pregnant women with diabetes during pregnancy.